Item analysis of office management and business service questions with Quest-software-based Rasch model - Haqiqi, Syaefa Habsyah Nur Maulida; Ismiyati, Ismiyati (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study aims to analyze the quality of items in the final summative assessment for Office Management and Business Services by applying the Rasch model to examine item fit, difficulty level, and reliability. A descriptive quantitative method was employed with 34 grade XI MPLB students at SMK Widya Praja Ungaran and 25 test items. The results show that 15 items (60%) fit the Rasch model (INFIT MNSQ 0.77–1.33), whereas 10 items (40%) could not be analyzed because they had no score variation. Based on threshold values, item difficulty consisted of 6 difficult, 3 moderate, 2 easy, and 4 very easy questions, with a range from -3.57 to 1.94. All analyzed items passed the fit test (OUTFIT t ≤ 2.00). The findings indicate good item reliability (0.84) but very low person reliability (0.00), suggesting inconsistent responses. It is concluded that the test quality is generally good, yet requires a more balanced difficulty distribution, improved learner consistency, and prior expert review to produce more accurate assessment results.